Presidential address - Hope, A. D. (Alec Derwent), 1907-2000; Australian Association for the Teaching of English ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1967)
The Australian association for the teaching of English has become increasingly influential since its founding. However, it is still not considered professional because of its lack of recognition as the organization entrusted with responsibility for the community's interests in the field of English education. The first step toward making it such a body is to bring together, in one organization or affiliation of organizations, all the members of the English-teaching profession, including the university teachers of English. At the same time, teachers in the elementary and secondary schools must enter the field of research and critical inquiry. Teachers must ask and seek to answer such fundamental questions as--(1) is English, properly speaking, a "subject" at all, (2) what don't we teach that we should, and (3) what could we do better by not teaching. When we know the answers to these questions we may be led to relinquish some of our elaborate teaching technIQues because the reasons for which we have perfected these technIQues are no longer valid. Research, for example, may show that pre-university students are incapable of developing adequate critical judgments in literature, and, therefore, we should develop students' appreciation for literature and train potential writers much like athletes. On the other hand, research might indicate that critical judgment can be developed only by the old technIQues of authoritarian drill and training in the skills and knowledge upon which culture and taste depend. Teachers must, therefore, be open-minded and willing to give up traditions and teaching technIQues if they prove to be delusions. This article appeared in "English in Australia," number 5, August 1967. (dl)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Research; English Curriculum; English Instruction; Literature Appreciation; Literature Programs; Methods Research; Professional Associations; Teaching Methods; Australian Association for the Teaching of English